The incidence of fatal fetal anomalies associated with perinatal mortality in Ireland. (7th February 2020) - Power, Stacey; Meaney, Sarah; O'Donoghue, Keelin
Abstract: Objective: The term fatal fetal anomaly (FFA) describes a condition likely to lead to death of the fetus in utero or within 28 days of birth. This study aimed to identify what congenital anomalies are responsible for perinatal death and whether they are classified as an FFA in accordance with criteria outlined in Irish legislation. Methods: Anonymised data pertaining to perinatal deaths from 2011 to 2016 in Ireland were obtained from the National Perinatal Epidemiology Centre. Secondary data analysis was conducted using SPSS. Results: Of the 2638 perinatal deaths, 939 (36%) had a congenital anomaly. Nearly half was chromosomal (43%, n = 406 of 939) with 36% of the cases (n = 333 of 938) having more than one anomaly. Additional information was available for 777 of these congenital anomaly, of which 42% (n = 328) could be classified an FFA. Conclusion: This study identified that less than half of the congenital anomalies could be classified as an FFA; however, all were fatal. This acknowledges the complexity of these cases. In isolation, the congenital anomaly may not be fatal, but combined as multiorgan system anomalies, it is. Knowledge is required to inform clinical practice and counselling of parents who receive such a diagnosis.